2005
DOI: 10.1200/jco.2005.00.463
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Injection of Dendritic Cells Engineered to Secrete Interleukin-12 by Recombinant Adenovirus in Patients With Metastatic Gastrointestinal Carcinomas

Abstract: PurposeTo evaluate the feasibility and safety of intratumoral injection of autologous dendritic cells (DCs) transfected with an adenovirus encoding interleukin-12 genes (AFIL-12) for patients with metastatic gastrointestinal carcinomas. Secondarily, we have evaluated biologic effects and antitumoral activity.Patients and MethodsSeventeen patients with metastatic pancreatic (n = 3), colorectal (n = 5), or primary liver (n = 9) malignancies entered the study. DCs were generated from CD14+ monocytes from leukaphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(121 citation statements)
references
References 55 publications
2
118
0
1
Order By: Relevance
“…Interleukin-12 is critical for therapeutic immunity against cancer (Mazzolini et al, 2003). Artificial enhancement of IL-12 production by DC strengthens elicited immunity and therapeutic potential (Melero et al, 1999;Mazzolini et al, 2005). Therefore, selective inhibition of IL-12 is likely to be suppressive for cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-12 is critical for therapeutic immunity against cancer (Mazzolini et al, 2003). Artificial enhancement of IL-12 production by DC strengthens elicited immunity and therapeutic potential (Melero et al, 1999;Mazzolini et al, 2005). Therefore, selective inhibition of IL-12 is likely to be suppressive for cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been successfully used in both preclinical 41 and clinical trials. [42][43][44] The commonly used methods include intratumoral injection of IL-12 plasmid DNA, 43 peritumoral injection of IL-12-producing autologous fibroblasts 42 or autologous tumor cells, 45 and intratumoral injection of dendritic cells secreting interleukin-12. 44 The response rate ranges from 6 to 89% depending on the tumor types and method of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] The commonly used methods include intratumoral injection of IL-12 plasmid DNA, 43 peritumoral injection of IL-12-producing autologous fibroblasts 42 or autologous tumor cells, 45 and intratumoral injection of dendritic cells secreting interleukin-12. 44 The response rate ranges from 6 to 89% depending on the tumor types and method of delivery. Intratumoral injection of IL-12 plasmid DNA in patients with advanced malignant melanoma, 43 and peritumoral injection of IL-12-producing autologous fibroblasts in patients with disseminated cancer 42 have achieved 89% (8/9) and 56% (5/9) response rate, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7,17 In a recent clinical trial conducted in patients with advanced primary or metastatic liver cancer, monocyte-derived DCs engineered with adenoviral vector encoding IL-12 were injected directly into the tumor. 18 In this trial, 3 monthly doses of the transduced cells were administered, and it was expected that, after intratumoral injection, DCs would take up tumor antigens and migrate to regional lymph nodes to stimulate an antitumor T-cell response that would be facilitated by the in situ production of IL-12. In this trial, the observed antitumor effect was very poor.…”
Section: Induction Of Antitumor and Antiviral Immunity Using Engineermentioning
confidence: 99%